TINJAUAN YURIDIS TERHADAP KONSTRUKSI HUKUM BADAN USAHA MILIK DESA (BUMDesa) DI KABUPATEN BANYUMAS - Rizky Priambodo (Jurnal Idea Hukum, 2019)
Village-Owned Enterprises (BUMDesa) in the legislation do not specifically explain the form of legal entity, type of company on BUMDesa, form of BUMDesa accountability with BUMDesa business units, and types of civil legal entities in BUMDesa business units. Research entitled "Juridical Review of Legal Construction of Village-Owned Enterprises (BUMDesa) in Banyumas District" aims to analyze the legal construction of Village-Owned Enterprises (BUMDesa) and to analyze the implementation of the formation of Village-Owned Enterprises in Banyumas Regency, provide information to BUMDesa which will be formed so that there is no law violation.The research method with normative juridical law research and research specifications is prescriptive. Data collection methods are literature studies or literature. The method of presenting data in the form of a description that is arranged systematically and the method of analysis used instudy thisis a qualitative normative analysis method.BUMDesa is constructed that BUMDesa is a Company and Business Entity because it meets the characteristics of the company, namely, aiming to make a profit, continuously, owning an organization. BUMDesa is a public legal entity because it was formed through village regulations. BUMDesa is a public legal entity in the form of a Public Corporation because it is identical with the characteristics of a PERUM-shaped BUMN. BUMDesa's accountability with the BUMDesa Business Unit is a group company because BUMDesa as the holding company has an economic unit with the BUMDesa business unit and is separated juridically between BUMDesa and the BUMDesa Business Unit. BUMDesa implementation in Banyumas Regency is that the application of laws and regulations on BUMDesa in Banyumas Regency is partly implemented, namely BUMDesa is formed through legislation namely Perdes which is not divided into shares, and the establishment of a civil legal entity in the BUMDesa business unit has not been implemented in large numbers.Conclusion, the construction of BUMDesa is in the form of a Public Legal Entity in the form of a Perumdes, with the form of accountability with the BUMDesa business unit in the form of a group company. Part of the implementation of BUMDesa in Banyumas District has been implemented in accordance with the prevailing laws and regulations.